Antidiabetic Therapy in End‐Stage Renal Disease. Issue 4 (21st April 2015) - Boyle, Suzanne M.; Simon, Barbara; Kobrin, Sidney M.
Abstract There has been substantial growth in the variety of available antidiabetic agents during the last decade and a half. The role of these newer agents in patients with diabetes and end‐stage renal disease (ESRD) population, and their relative benefits and risks in this population compared to patients without ESRD are not yet clear. This stems from the altered state of glucose homeostasis in ESRD, which places patients at high risk for hypoglycemia and, in certain situations, hyperglycemia. In addition, there is a dearth of evidence to support a benefit of tight glycemic control on either micro‐ or macrovascular outcomes in ESRD patients; furthermore, the metrics by which glycemic control is conventionally measured are less valid in ESRD. In this review, we will discuss noninsulin and insulin‐based therapies as well as unique challenges, contraindications, advantages, and disadvantages to their use in ESRD. We will also review issues pertinent to both hemodialysis (HD) and peritoneal dialysis (PD) patients.